How Self-Concept and Ego Can Be Evaluated and Discussed Within Consumer Habits - Harvey Bolger (Design Journal, 2026)
The impact that self-concept and ego have on consumeristic habits often goes unnoticed each day, as mundane purchasing habits become invisible and methodical. Do we truly acknowledge the implications behind what we buy? We may all resonate with how marketing can shape our perspectives, particularly given the societal awareness of social media and its influence, but are we truly honest with ourselves when we look deeper into our own actions? This study identifies the ways in which self-concept and ego can manipulate individual actions and viewpoints in relation to consumerism, drawing out pivotal theoretical understandings within the context of today through literature review, speculative design, autoethnography, and critical design practice. It therefore offers a new perspective within the self-concept and ego lens, bringing a speculative global design attitude to the largely theoretical and academic groundings of the topic, and by opening this new scope onto the relationship between the self, the ego, and consumption, it allows for a personal and societal shift in understanding the impacts and manipulations that consumption can have, creating a speculative space for reflection and critical assessment.